PENGARUH KUALITAS PELAYANAN DIVISI TICKETING TERHADAP KEPUASAN PELANGGAN DI PT. TUNGGAL TOUR AND TRAVEL PEKANBARU - Cindy Abama Rumengan; Andi M Rifiyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study aims to determine whether the dimensions of service quality that is tangible, reliability, responsiveness, assurance, and empathy influence on consumer satisfaction, PT. Tunggal Tour and Travel and analyze the most dominant factor in influencing customer satisfaction PT. Tunggal Tour and Travel. The population in this study is the customers who come to PT. Tunggal Tour and Travel. Samples were taken of 100 respondents by using the technique of Non-Probability Sampling with Accidental sampling approach, the sampling technique is based on chance, ie, who happened to meet with researchers can be sampled as it sees fit. Based on the research results, it is obtained the following regression equation: Y = -3.861 + 0.313 0,318 x1 + x2 + x3 + 0.284 0.174 0.108 x4 + x5 + e. Based on statistical data analysis, the indicators in this study are valid and variables are reliable. In the classical assumption test, regression models multikolonieritas free, does not occur heteroscedasticity, and normal distribution. Individual sequence of each of the most influential variable is the variable responsiveness with regression coefficient of 0.318, and reliability with a regression coefficient of 0.313, followed by empathy with a regression coefficient of 0.284, and the assurance with regression coefficient of 0.174 whereas the most influential variable tangibles with a low regression coefficient is 0.108. PT. Single Tour and Travel needs to maintain the elements that have been considered good by customers as well as the need memperbaikihal that are still lacking.Key words: quality of service, tangible, reliability, responsiveness, assurance, empathy, customer satisfaction.